Sekuen Nukleotida Gene Shiga like toxin-2 dari Isolat Lokal Escherichia coli O157:H7 asal Hewan dan Manusia (NUCLEOTIDES SQUENCES OF SHIGA-LIKE TOXIN 2 GENES OF ESCHERICHIA COLI O157:H7 LOCAL ISOLATES ORIGINATED FROM ANIMALS AND HUMAN) - Suardana, I Wayan; Widiasih, Dyah Ayu; Pinatih, Komang Januartha Putra (Jurnal Veteriner, 2017)
Animals/livestock, especially cattle, are known as the main reservoir of Escherichia coli O157: H7. As the only one of zoonotic E. coli , the pathogenicity of these bacteria is determined by its ability to produce one or more very potent cytotoxin known as Shiga-like toxin (Stx) or verocytotoxin, particularly of the Stx2 type that is closely related to the incidence of hemolytic uremic syndrome (HUS) in humans. This study analyzed the nucleotide sequences of stx2 gene between isolates from animals and humans in an effort to assess the potential zoonoses of the agent. The research activity was initiated by cultivating 20 isolates of E. coli O157:H7 collection based on result in the previous study i.e. 2 isolates originated from cattle feces, 2 isolates originated from beef, 2 isolates originated from chicken feces, 2 isolates originated from human feces, and 12 non-clinical isolates originated from human fecal who were suffering with renal failure. All isolates were confirmed on selective medium Sorbitol MacConkey Agar (SMAC) followed by testing on aglutination O157 latex test, and H7 antisera. Molecular analysis of stx2 gene covering open reading frame (ORF) of the stx2 gene was performed using the primer which was designed by researcher i.e. Stx2 (F)/Stx2 (R). The results showed, there were 2 isolates i.e. KL-48 (2) originated from human feces and SM-25 (1) originated from cattle feces were positive for carrying a stx2 gene, which was marked by the 1587 bp PCR product. Analysis of sequencing showed both isolates had identical to stx2 nucleotide squences with E. phaga 933 as well as E. coli ATCC 933. These results indicate the both local isolates are potential as zoonotic agents with clinical effects similar to E. phaga 933 and E. coli ATCC 43894. ABSTRAK Hewan ternak khususnya sapi, dikenal sebagai reservoir utama Escherichia coli O157:H7. Sebagai satu-satunya serotipe E. coli yang bersifat zoonosis, patogenitas bakteri ini ditentukan oleh kemampuannya untuk menghasilkan satu atau lebih cytotoxin yang sangat potensial yang dikenal dengan nama Shiga-like toxin (Stx) atau verocytotoxin, khususnya dari jenis Stx2 yang terkait erat dengan kejadian hemolytic uremic syndrome (HUS) pada manusia. Studi ini bertujuan menganalisis susunan nukleotida dari gen stx2 antara isolat asal hewan dan manusia dalam upaya mengkaji potensi zoonosis yang ditimbulkannya. Kegiatan penelitian diawali dengan kultivasi 20 isolat E. coli O157:H7 koleksi hasil penelitian sebelumnya dengan rincian dua isolat asal tinja sapi, dua isolat asal daging sapi, dua isolat asal tinja ayam, dua isolat asal tinja manusia non-klinis, dan 12 isolat asal tinja manusia klinis (asal penderita gagal ginjal). Isolat sebanyak 20 tersebut dikonfirmasi pada media selektif sorbitol MacConkey agar (SMAC) yang dilanjutkan dengan uji latex O157 aglutination test serta uji antiserum H7. Analisis molekuler komplit gen stx2 yang meliputi open reading frame (ORF) dari gen stx2 dilakukan menggunakan primer rancangan peneliti yaitu Stx2(F)/Stx2(R). Hasil penelitian menunjukkan bahwa ada dua isolat yaitu KL-48 (2) asal tinja manusia dan SM-25 (1) asal tinja sapi positif membawa gene stx2 yang ditandai dengan produk PCR 1587 bp. Analisis hasil sekuensing menunjukkan kedua isolat memiliki susunan gene stx2 yang identik dengan E. phaga 933 dan E. coli ATCC 43894. Hasil ini mengindikasikan kedua isolat lokal berpotensi sebagai agen zoonosis dengan efek klinis yang serupa dengan E. phaga 933 dan E. coli ATCC 43894.
Keywords: E. coli O157:H7; gene stx2; hemolytic uremic syndrome; zoonoses